Inherited Thrombophilia is Associated With Deep VeinThrombosis in a Colombian Population (2006)
ABSTRACT: The development of venous thromboembolism is influenced by a variety of genetic and environmental risk factors. A few studies have ascertained whether thrombophilic defects are risk factors for venous thromboembolism in Latin American populations with a variable degree of admixture, such as the Colombian population. To address this issue, we con-ducted a case–control study involving 100 consecutive patients with deep vein thrombosisand 114 healthy controls from the Hospital Universitario San Vicente de Paúl, Medellín, Colombia. Activated protein C resistance (APC resistance) was detected in 25/99 patients vs. 6/114 controls (OR56.08, 95% CI52.23–17.47). Ten of 100 patients carried the factor V Leiden mutation vs. 1/114 controls (OR512.56, 95% CI51.61–267). APC resistance was associated with the factor V Leiden mutation in only 10/25 patients. The prothrombinG20210A mutation was found in 4/100 patients, but none of the controls (P< 0.05). There was no significant difference in the proportion of homozygous carriers of methylenetetrahydrofolate reductase C677T variant among patients and controls. In conclusion, in our studied population, factor V Leiden, APC resistance, and prothrombin G20210A were associated with an increased risk of deep vein thrombosis. However, the frequencies of these thrombophilic defects and of APC resistance associated with factor V Leiden was lower than the corresponding frequencies previously reported for Caucasian populations. Further study is required to assess the influence of ethnicity on thrombophilia.